Akidah, akhlak dan hubungannya dengan tingkah laku belia di Institusi Pengajian Tinggi - Tan, Rohana; Zainal Abiddin, Norhasni (Pusat Pengembangan dan Publikasi Karya Ilmiah (P3KI) Sekolah Pascasarjana, Universitas Pendidikan Indonesia, 2014)
This article discusses the concept and the definition of adolescence and youth; the concept of creed; the concept of religious behavior and relationship to youth behavior. The discussion also include the theory of adolescence and youth development; theories of human behavior such as Theory of Psychoanalysis, Social Learning Theory and Behavioral Theory of Islam. These theories related to psychology, learning and human and why they behave in such a way. Positive behavior and negative behavior are associated with the practice of religious behavior and creed. Thus, by understanding the concept of youth, creed, religious behavior theories and human behavior theories, it is hope that this article can give an overview of problems and issues in youth and adolescence and can be a reference in the aspects of adolescence and youth development.